Edukasi Sumur Resapan Air Limbah Rumah Tangga Untuk Lingkungan Sehat Di RW 02 Desa Marengmang Kecamatan Kalijati Subang - Ernawan, Deny; Sugeng Sutikno; Eliya Sari (Fakultas Ilmu Administrasi Universitas Subang, 2025)
Abstrak Kebersihan lingkungan adalah keadaan di mana lingkungan bebas dari kotoran, termasuk di dalamnya debu, sampah, dan bau. Lingkungan yang bersih dapat menjadikan kita terhindar dari berbagai macam penyakit. Dalam menjaga kebersihan lingkungan hidup tidak hanya diri kita sendiri, tetapi juga mencakup semua elemen yang ada di masyarakat. Kurangnya kesadaran masyarakat terhadap lingkungan sangat familiar untuk saat ini. Kebanyakan dari mereka berfikir secara parsial dan hanya ingin menguntungkan diri sendiri, seperti masalah pembuangan sampah yang tidak pada tempatnya, pembuangan limbah pabrik, polusi udara, pencemaran air, dan lain-lain. Kasus-kasus yang menyangkut masalah kebersihan dalam lingkungan hidup yang selalu mempengaruhi kesehatan masyarakat setiap tahunnya selalu meningkat. Masyarakat juga perlu meningkatkan lingkungan hidup dan bisa terselenggaranya kegiatan pembangunan yang dapat membantu daya lahan secara serasi dan berkelanjutan. Untuk itu pemberian penyuluhan terkait edukasi pembuatan sumur resapan diharapkan dapat menjadi upaya menyadarkan masyarakat akan pentingnya kesehatan lingkungan sekaligus memberikan pengetahuan bagaimana cara merealisasikannya. Pendekatan ini diharapkan untuk memberdayakan potensi lokal, memupuk rasa milik diri, meningkatkan nilai manfaat, dan menjamin keberlanjutan. Kata kunci: Kesehatan Masyarakat, Standar Kesehatan, Sumur Resapan Abstract Environmental cleanliness is a condition where the environment is free from dirt, including dust, garbage, and odors. A clean environment can make us free from various diseases. Keeping the environment clean is not only for ourselves, but also for all elements of society. The lack of public awareness of the environment is very familiar today. Most of them think partially and only want to benefit themselves, such as the problem of improper waste disposal, factory waste disposal, air pollution, water pollution, and others. Cases of environmental hygiene problems that always affect public health are increasing every year. The community also needs to improve the environment and be able to carry out development activities that can help the earth's energy in a harmonious and sustainable manner. For this reason, providing education related to infiltration well construction is expected to be one of the efforts to increase public awareness of the importance of environmental health and provide knowledge on how to make it happen. This approach is expected to empower local potential, foster a sense of belonging, increase the value of benefits, and ensure sustainability. Keywords: Public Health, Health Standards, Infiltration Wells Abstract Environmental cleanliness is a condition where the environment is free from dirt, including dust, garbage, and odors. A clean environment can make us free from various diseases. Keeping the environment clean is not only for ourselves, but also for all elements of society. The lack of public awareness of the environment is very familiar today. Most of them think partially and only want to benefit themselves, such as the problem of improper waste disposal, factory waste disposal, air pollution, water pollution, and others. Cases of environmental hygiene problems that always affect public health are increasing every year. The community also needs to improve the environment and be able to carry out development activities that can help the earth's energy in a harmonious and sustainable manner. For this reason, providing education related to infiltration well construction is expected to be one of the efforts to increase public awareness of the importance of environmental health and provide knowledge on how to make it happen. This approach is expected to empower local potential, foster a sense of belonging, increase the value of benefits, and ensure sustainability. Keywords: Public Health, Health Standards, Infiltration Wells